Risk adjusted therapy in chronic lymphocytic leukemia: a phase II cancer trials Ireland (CTRIAL-IE [ICORG 07-01]) study of fludarabine, cyclophosphamide, and rituximab therapy evaluating response adapted, abbreviated frontline therapy with FCR in non-del(17p) CLL. Issue 6 (3rd June 2018) - Appleby, Niamh; O'Brien, David; Quinn, Fiona M.; Smyth, Liam; Kelly, Johanna; Parker, Imelda; Scott, Kathleen; Cahill, Mary R.; Crotty, Gerard; Enright, Helen; Hennessy, Brian; Hodgson, Andrew; et al.
Abstract: Minimal residual disease negative complete response (MRD-negative CR) provides an early marker for time to treatment failure (TTF) in CLL treated with fludarabine, cyclophosphamide, and rituximab (FCR). MRD was assessed after four FCR cycles (FCR4); MRD-negative CR patients discontinued treatment. Fifty-two patients (35M; 17F) were enrolled. Eighteen (18/52; 34.6%) patients reached MRD-negative CR after FCR4 and 29/52 (55.8%) were MRD-negative CR at end of treatment (EOT). Median TTF was 71.1 months (95% CI 61.3–84.1 months), with median overall survival not reached. Mutated immunoglobulin heavy chain gene rearrangements ( IGHV ) were associated with early MRD-negative remissions, translating into prolonged TTF. Unmutated- IGHV, mutated- SF3B1 and mutated- NOTCH1 were associated with shortened TTF. No TTF difference was observed between patients in MRD-negative CR after four versus six cycles (82.2 versus 85.3 months, p  = .6306). Abbreviated FCR therapy is effective for patients achieving early MRD-negative remissions. Interim MRD assessment assists in personalizing therapy and reducing chemotherapy-associated toxicity.